Comparative Evaluation of Natural vs. Synthetic Membranes in GTR: In Vitro Cell Proliferation Study - Dr Nimrah Khalil, Dr Syeda Rabia Rahat Geelani, Dr Muhammad Wajahat Ghafoor Chaudary,Dr Rafey Ahmad Jameel, Dr. Shah Salman Khan, Dr Abdul Qadir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Guided Tissue Regeneration (GTR) membranes are integral in periodontal and oral regenerative therapies. Natural membranes (collagen-based) and synthetic membranes (polylactic/polyglycolic acid) are widely used, but their comparative impact on cellular proliferation remains unclear.